(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
In the flora of Ukraine, the order Euphorbiales includes two families, Euphorbiaceae and Phyllanthaceae. The family Euphorbiaceae is represented by five genera, namely Acalypha, Chrozophora, Euphorbia, Мercurialis, Ricinus, comprising 61 species of native and cultivated flora. The genus Acalypha is represented in Ukraine by an alien species of East Asian origin, A. australis. The genus Chrozophora in the flora of Ukraine also includes one species, C. tinctoria, whose synonyms are C. hierosolymitana and C. obliqua. Significant nomenclatural changes occurred in the genus Euphorbia. In particu-lar, E. jasiewiczii, previously cited in Ukrainian taxonomic literature as a sepa-rate species, is a taxonomic synonym of E. carpatica. Synonyms of E. chamaesyce are E. canescens and E. massiliensis (the latter was treated as an accepted name for pubescent plants of E. chamaesyce). Euphorbia tyraica is a synonym of E. cyparissias. Euphorbia davidii is a kenophyte of North Ameri-can origin, which has been widespread now in almost all regions of Ukraine. It was erroneously referred earlier to E. dentata, from which it differs in the nature of seed sculpture. There was supported the interpretation of E. lingulata as a synonym of E. epithymoides, E. kotovii as a synonym of E. erythrodon, E. pseudoglareosa as a synonym of E. × goldei, E. klokovii, E. pseudovillosa, E. villosa, and E. volhynica as synonyms of E. illirica, E. cretophila as a synonym of E. petrophila, E. klokoviana as a synonym of E. stepposa, E. graeca as a synonym of E. taurinensis, E. kitaibelii, E. pseudovirgata, and E.waldsteinii as synonyms of E. virgata. The species E. esula was also previously given under different synonimic names (such as E. borodinii, E. kaleniczenkoi, E. tristis) for the flora of Ukraine. At the same time, E. falcata and E. helioscopioides [= Euphorbia helioscopia L. subsp. helioscopioides (Loscos & J.Pardo) Nyman], which are widespread in Ukraine (including Crimea), are not listed in POWO (as of 2024) for unknown reasons. New for Ukraine are the records of E. glyptosperma (xenophyte of North American origin), E. hirsuta (reported for Crimea), and E. serpens (also xenophyte of North American origin). The species E. saratoi, which is widespread throughout Ukraine as a weed in the fields and gardens, was previously identified as E. virgultosa, that in turn was mistakenly synonymized with E. virgata. From E. virgata, first described from Hungary, E. saratoi differs well with the shape of leaves, flower and seed morphology. The family Phyllanthaceae is presented in Ukraine by two genera, each including one species.